Mengenal Kebudayaan Suku Bugis - Fatmawati, Fifi; Kurnia, Heri (CV. Kurnia Grup, 2023)
Bugis tribal culture is a very complex reality in the lives of Indonesian people. The Bugis tribe, as part of the Deutero Malay group, came to the archipelago after the first wave of migration from mainland Asia, especially Yunan. The name